Development of supply chain based fuel cycle inventory model for the Philippines - Sy, Alexis Mervin T. (Animo Repository, 2017)
Life cycle inventory (LCI) is a crucial phase of life cycle assessment (LCA) which deals with the quantification of relevant system inputs and outputs. In practice, established models and inventories are normally utilized by researchers and practitioners to facilitate LCA studies. However, existing models and inventories range mostly for non-Philippine applications. Given the diverse application of fossil fuels, the study developed a customizable supply chain based fuel cycle model coded in spreadsheet to establish the fuel cycle inventory of fossil fuels (i.e. coal, natural gas, and crude oil products) and power generation in the Philippines. The fuel cycle analysis generated were compared to results in GREET using USA as level 1 country source and revealed larger values due to supply chain considerations, assumptions, and system boundaries assigned in the study. The model was then used in the fuel cycle analysis of Business As Usual (BAU) and Low Carbon Scenario (LCS) power generation in the Philippines to further validate the model. The fuel cycle inventory is envisioned to provide more accurate and comprehensive analysis of LCA fuel application in the Philippines.